Large Particle Flotation In The Recently Developed Shallow Air Cell - Paul R. Smith (Society for Mining, Metallurgy & Exploration, 1969)
The theoretical requirements for the flotation d large particles are discussed. A flotation machine is described which has components which meet many of the theoretical requirements for the flotation of large particles. The machine's salient features include multiple fine-bubble attachment, froth level feeding, quiescence, shallow depth, and short flotation time. Test conditions and results are presented for the laboratory flotation of 10 mesh phosphate, 4 mesh potash, and 1/2 inch coal. In addition, test conditions and results of pilot plant flotation of minus 14 plus 35 mesh phosphate and minus 14 plus 150 mesh phosphate are also presented.